2022
DOI: 10.3390/constrmater2010005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Prediction and Durability on the Chloride Penetration in Cementitious Materials with Blast Furnace Slag as Cement Addition

Abstract: Blast furnace slag (BFS) is a mortar additive in which the utilization of varied curing conditions and the basicity of BFS determine the fineness of the resulting mortar and, thereby, its salt prevention properties. This study evaluates and compares the salt-prevention properties of mortar prepared by either steam curing or water curing. The physical properties, for example, the BFS fineness, revealed the factors significantly affected by basicity that influence the salt-preventive properties of mortar in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The issue of the durability of concretes and mortars based on slag has also received much attention [26,30,[32][33][34][35][36]. At the same time, these characteristics of solutions with the addition of DHS as frost resistance [30] and resistance to chlorides [34], sulfates [33], and various acids [26,32] were studied.…”
Section: Holding Time Daysmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of the durability of concretes and mortars based on slag has also received much attention [26,30,[32][33][34][35][36]. At the same time, these characteristics of solutions with the addition of DHS as frost resistance [30] and resistance to chlorides [34], sulfates [33], and various acids [26,32] were studied.…”
Section: Holding Time Daysmentioning
confidence: 99%
“…The issue of the durability of concretes and mortars based on slag has also received much attention [26,30,[32][33][34][35][36]. At the same time, these characteristics of solutions with the addition of DHS as frost resistance [30] and resistance to chlorides [34], sulfates [33], and various acids [26,32] were studied. Moreover, the authors of many works consider the joint effect of GBFS and other additives (ash, limestone, gypsum, nanosilica) on the formation of the micro-and macrostructure of materials based on them and their physical and mechanical characteristics [10,28,30,[35][36][37][38].…”
Section: Holding Time Daysmentioning
confidence: 99%
“…Microsilica, a by-product of silicon or ferrosilicon production, presents as amorphous silica (SiO 2 ) in spherical particle form [1][2][3][4][5][6][7][8][9][10]. Widely utilized within the construction industry, microsilica serves as a modifying component in concrete production, leveraging its chemical composition and physical attributes as a highly active pozzolan [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The extensive introduction of various highly effective chemical and mineral additives has led to significant advancements in modern concrete technology.…”
Section: Introductionmentioning
confidence: 99%
“…Cement usage surpasses 4000 million tons annually and is projected to reach approximately 6000 million tons by 2060 [12,13], greatly contributing to climate change through greenhouse gas emissions [13][14][15]. To address this, agricultural and industrial wastes, such as rice husk ash (RHA), sugarcane bagasse ash, and olive oil ash, are utilized to partially substitute OPC in the production of green concrete [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The strength at 28 days may be smaller than the 28-day strength of OPC concrete when the GGBFS content is greater than 50% [ 10 ]. Based on the principle that the higher the specific surface area, the better the hydration process for cementitious materials, Subpaasa Prang et al demonstrated that increasing the Blaine value of BFS boosts the concrete’s compressive strength [ 17 ]. As a result, while producing BFSC, more finely grinding is among the primary techniques to effectively improve the resulting concrete’s strength [ 18 ].…”
Section: Introductionmentioning
confidence: 99%